Social isolation as a significant risk factor for depression in colorectal cancer patients post-colostomy: a cross-sectional study - Zou, Jianmei; Jia, Haina; Wang, Jing; Li, Yanxia (Frontiers in Psychiatry, 2025)
ObjectiveColorectal cancer is a leading global health concern, with significant physical and psychosocial impacts on patients. Many CRC patients undergo colostomy procedures, which can lead to lifestyle changes and an increased risk of depression. Social isolation, a detachment from social networks, has been linked to depression in various chronic illnesses but remains underexplored in this specific patient group. This study aims to investigate the association between social isolation and depressive symptoms in patients with colorectal cancer following colostomy.MethodsA cross-sectional study design was employed, enrolling colorectal cancer patients who underwent colostomy from January 2020 to January 2023. Clinical and questionnaire data were collected. The Chinese version of the Patient Health Questionnaire (PHQ-9) was utilized to assess depression, while the Lubben Social Network Scale (LSNS-6) evaluated social isolation. Demographic characteristics, clinical variables, psychosocial adaptation, and social support were also gathered. Univariate and multivariate logistic regression analyses, along with subgroup analyses, were conducted to identify risk factors influencing depression.ResultsA total of 290 patients were included, among which 139 were diagnosed with depression. Both univariate and multivariate analyses indicated that tumor stages III-IV (OR=1.94, 95% CI: 1.14-3.30) and prolonged colostomy duration (OR=4.04, 95% CI: 1.87-8.72) are independent risk factors for depression, while social isolation (OR=0.24, 95% CI: 0.13-0.44) is a significant protective factor. The prevalence of depression was significantly higher in the social isolation group compared to the non-social isolation group (58.8% vs. 43.8%, P=0.024). The prevalence of depression was significantly higher in the social isolation group compared to the non-social isolation group (58.8% vs. 43.8%, P=0.024). Subgroup analyses revealed significant interactions, with social isolation showing stronger inverse associations with depression in males, individuals aged <60 or >70, divorced/widowed/single patients, and those with low social support.ConclusionSocial isolation represents a crucial risk factor for depression in colorectal cancer patients following colostomy. Healthcare professionals should prioritize the assessment of patients’ social isolation and implement targeted interventions to mitigate the risk of depression.